(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
An author’s references may indicate relationships of opposition, acceptance or refusal between the knowledge being constructed and the available knowledge. References can also indicate the relationships an author has to admit to have his work accepted. Skinner’s references, on his 35 publications, between 1930 and 1938, were analyzed to evaluate the possible existence of Skinner’s intellectual isolation during this period. 275 references were identified, with 151 different titles referred, and, including Skinner, 106 different authors. Skinner was the most referred author (126 references). On Skinner’s publications of experimental studies (19 publications), the great majority of the references were to his own previous work. The authors’ conclusion is that due to the methodological and conceptual peculiarities of Skinner’s work, during this period, he had to rely on his own work.